自傷行為による舌潰瘍を契機に診断に至った小児自閉症スペクトラム障害の１例 - 濱田, 良樹; 新井, 剛; 市川, はるの; 木村, 愛理; 江口, 貴紀; 齋藤, 知之 (日本口腔外科学会雑誌, 2025)
In many pediatric cases of oral self-mutilation, psychiatric disorders may be the main causative factor. Recently, the presence of sensory processing disorders as characteristics of autism spectrum disorder has attracted attention, and it has been added to the diagnostic criteria. We report a pediatric case of autism spectrum disorder diagnosed through tongue ulceration due to self-mutilation. The patient was a 7-year-old boy who visited our clinic with the chief complaint of intractable ulcer with itching on the tongue tip. We attempted to consult a pediatric psychiatrist based on a diagnosis of tongue ulceration resulting from self-mutilation due to sensory abnormalities. However, we encountered difficulties since the department of pediatric psychiatry refused his registration because he had no history of psychiatric consultation or referral by a dentist. Meanwhile, the tongue ulceration rapidly deteriorated and abnormal behavior with suicidal ideation became apparent. We desperately explained the urgency of the situation to a pediatric psychiatrist, and he was finally accepted by a specialized hospital for pediatric psychiatry. Consequently, he was definitively diagnosed as having pediatric autism spectrum disorder and received appropriate medication. As a result, the abnormal behavior and tongue ulceration disappeared. Since then, there has been no recurrence of symptoms for 3 years and 5 months.